The Support System the Credit Worthiness of the Decision on Customers in A Analitical Hierarchy Process (AHP) - Emha Nabilah Alparisa; Siti Mukodimah; Riki Riki (Journal of Intelligent Business and Technology Science (JIBTec), 2022)
The bank is a financial institution that sometimes pays low-interest loans to its customers. But because of the number of customers who wanted to obtain a loan, the banks often find it difficult to determine which you are openly declaring customers to enable them to should be able to access the loan was. A financial institution that among other things provides loans to its customers one of these is the additional loan from Bank Mandiri. The senior deputy governor of the bank the branch of Pringsewu building located on Jl. Ahmad Yani Pringsewu. To build the support system a decision which was made lots of standing around deciding for the feasibility of the provision of the credit will adopt the researchers used a method of AHP. Was used in the study a method of ahp in determining the feasibility of the provision of credit at a Bank Mandiri had initially agreed to. In the determination of for the feasibility of provision of credit will continue, there are several criteria on which to base the decision-making process aimed among other things at capacity, capital with pt bank Mandiri, cardiac condition, collateral, character. After determining the criteria of the next stage of is to include in the calculation of the hierarchy analytical these common (ahp), if a customer to enable them to with the highest value ones are gonna get.